2006
DOI: 10.1152/japplphysiol.01416.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of voluntary wheel running on circadian corticosterone release and on HPA axis responsiveness to restraint stress in Sprague-Dawley rats

Abstract: Adaptations of the hypothalamic-pituitary-adrenal (HPA) axis to voluntary exercise in rodents are not clear, because most investigations use forced-exercise protocols, which are associated with psychological stress. In the present study, we examined the effects of voluntary wheel running on the circadian corticosterone (Cort) rhythm as well as HPA axis responsiveness to, and recovery from, restraint stress. Male Sprague-Dawley rats were divided into exercise (E) and sedentary (S) groups, with E rats having 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
106
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(128 citation statements)
references
References 45 publications
20
106
2
Order By: Relevance
“…lation surgery (P Ͻ 0.05), as has previously been reported (14). However, following surgery, all groups continued to gain weight as expected.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…lation surgery (P Ͻ 0.05), as has previously been reported (14). However, following surgery, all groups continued to gain weight as expected.…”
Section: Resultssupporting
confidence: 83%
“…Thus, unlike with forced exercise, voluntary exercise may increase adrenal sensitivity to ACTH. In line with this hypothesis, we have previously shown that long-term wheel running (6 wk) in rats yields a normal GC response to restraint stress, despite attenuated ACTH levels (14). However, it is still unclear 1) if voluntary wheel running increases adrenal sensitivity to exogenous ACTH administration; 2) if the increased adrenal sensitivity to ACTH is sustained with prolonged training; and 3) how these apparent changes in adrenal sensitivity occur.…”
mentioning
confidence: 81%
See 3 more Smart Citations